Electrochemical immunosensor based on AuBP@Pt nanostructure and AuPd-PDA nanozyme for ultrasensitive detection of APOE4. Issue 13 (24th February 2020) - Liu, Yibiao; He, Guangli; Liu, Huili; Yin, Hang; Gao, Fengli; Chen, Jian; Zhang, Shouren; Yang, Baocheng
Abstract : An ultrasensitive sandwich-type electrochemical immunosensor based on AuBP@Pt nanostructures and AuPd-PDA nanozyme was developed for the detection of apolipoprotein E4 (APOE4) which was an important risk factor for Alzheimer's disease (AD). Abstract : An ultrasensitive sandwich-type electrochemical immunosensor based on AuBP@Pt nanostructures and AuPd-PDA nanozyme was developed for the detection of apolipoprotein E4 (APOE4) which was an important risk factor for Alzheimer's disease (AD). In this work, gold nanobipyramid coated Pt (AuBP@Pt) nanostructures were prepared and applied to electrochemical immunosensors as a substrate material. AuBP@Pt nanostructures have advantages of electrical conductivity and large electroactive area, which could greatly increase electron transfer rate. In previous work, we designed AuPd alloy modified polydopamine (AuPd-PDA) nanozyme which catalyzed the decomposition of hydrogen peroxide (H2 O2 ). AuPd-PDA nanozyme was used to label detection antibody due to excellent catalytic capability and stability in this new paper. And the concentration of APOE4 could be detected quantitatively by variation for transient current. As a result, the electrochemical immunosensor based on AuBP@Pt and AuPd-PDA exhibited a wide linear range from 0.05 to 2000 ng mL −1 and low detection limit of 15.4 pg mL −1 (S/N = 3). Furthermore, the designed biosensor displayed good selectivity in phosphate buffer saline (PBS) buffer solution or commercial goat serum, which provided a promising tool for early diagnosis of AD.